Influence of casual distributions on resonant properties of ensembles of nonlinear oscillators - Buts, V.A. (Вопросы атомной науки и техники, 2009)
It is shown, that properties of ensembles of nonlinear oscillators each of which makes chaotic movement, can
essentially differ from properties separate oscillators. In particular, is shown, that dynamics of average values of
ensembles can essentially depend on the statistical characteristics of separate oscillators. Показано, що властивості ансамблів нелінійних осциляторів, кожен з яких здійснює хаотичний рух, може
істотно відрізнятися від властивостей окремих осциляторів. Зокрема, показано, що динаміка середніх величин
ансамблів може істотно залежати від статистичних характеристик окремих осциляторів. Показано, что свойства ансамблей нелинейных осцилляторов, каждый из которых совершает хаотическое
движение, может существенно отличаться от свойств отдельных осцилляторов. В частности, показано, что
динамика средних величин ансамблей может существенно зависеть от статистических характеристик
отдельных осцилляторов.